Four-sensor droplet capable conductivity probe for measurement of churn-turbulent to annular transition flow. (August 2020) - Wang, Guanyi; Zhu, Qingzi; Ishii, Mamoru; Buchanan, J.R.
Highlights: A novel four-sensor conductivity probe is developed featuring with disperse liquid phase (droplets) detection capability and identifying whether the liquid phase is contiguous with the liquid film A first of a kind experimental dataset in the churn-turbulent and annular flow with 2D spatial distribution is established using the new probe The results are cross-checked against a vortex flow meter and rotameter for the superficial gas and liquid velocity, and the uncertainty is less than 10% and 20%, respectively The measured droplet size distribution agrees well with the model prediction Abstract: In churn-turbulent to annular transition two-phase flow, both gas and liquid phase exist in the form of either continuous field (gas core/liquid film) or dispersed field (bubble/droplet). The complexity of the flow structure makes it very difficult to obtain experimental data in the churn-turbulent to annular transition flow. A novel four-sensor conductivity probe has been designed to measure interfacial structures at the churn-turbulent to annular flow regime transition. The new probe incorporates a sensor close to the detection point to serve as a common electrode for the other four sensors. Relatively large droplets can be identified and distinguished from the continuous liquid phase such as a liquid ligament or a film attached to the wall. To satisfy the higher requirements of the probe signal quality for the churn-turbulent and annular transition flow, the probe circuit has been optimized for a faster signal response and less interference. The new probe was tested in a 200 mm × 10 mm channel with an inlet superficial gas velocity up to 19.91 m/s. The measurement results are cross-checked by area-averaging the local superficial liquid and gas velocities and comparing with the measurements from a vortex flow meter and rotameter. The error is less than 10% for the superficial gas velocity and less than 20% for the superficial liquid velocity. The measured droplet size distribution is compared with a previous model, and good agreement is obtained. The effect of superficial gas velocity on droplet and ligament volume fraction as well as interfacial area concentration are investigated using the local measurement results of the three churn-turbulent to annular flow conditions.